Cross reactivity and lethality neutralization of venoms of Indonesian Trimeresurus complex species by Thai Green Pit Viper Antivenom. (15th December 2017) - Tan, Choo Hock; Liew, Jia Lee; Tan, Nget Hong; Ismail, Ahmad Khaldun; Maharani, Tri; Khomvilai, Sumana; Sitprija, Visith
Abstract: Arboreal pit vipers of the Trimeresurus complex group are medically important species in Indonesia (west of Wallace's line), but there is no specific antivenom produced in the country for treating related envenomation. Instead, the exiting trivalent Indonesian antivenom, Biosave ® Serum Anti Bisa Ular (SABU, indicated for envenoming by Malayan pit viper, Javan spitting cobra and banded krait) is often misused to treat Trimeresus envenoming resulting in poor therapeutic outcome. Here, we investigated the cross-reactivity and neutralization capability of Thai Green Pit Viper Antivenom (GPVAV) against the venoms of four Indonesian Trimeresurus species. Consistently, the venoms of Trimeresurus ( Trimeresurus) insularis, Trimeresurus ( Trimeresurus) purpureomaculatus, Trimeresurus ( Parias) hageni and Trimeresurus ( Craspedocephalus) puniceus of Indonesia showed stronger immunoreactivity on ELISA to GPVAV than to Biosave ® . The findings correlated with in vivo neutralization results, whereby GPVAV was far more effective than Biosave ® in cross-neutralizing the lethality of the venoms by a potency of at least 13 to 80 times higher. The efficacy of GPVAV is partly attributable to its cross-neutralization of the procoagulant effect of the venoms, thereby mitigating the progression of venom-induced consumptive coagulopathy. The paraspecific effectiveness of GPVAV against Trimeresurus species envenoming in Indonesia await further clinical investigation. Graphical abstract: Highlights: Pit viper envenoming by Trimeresurus sp. is serious in Indonesia. Thai Green Pit viper Antivenom (GPVAV) was tested for cross-neutralization. GPVAV showed strong immunoreactivity toward Indonesian Trimeresurus venoms. Lethality and procoagulant effects were effectively cross-neutralized.